Transforming Reading into Digital Performance: Instagram-Based Oral Retelling for EFL Reading Comprehension - Nuraeningsih; Rusiana; Muh. Syafei; Sibhekinkosi Anna Nkomo; Kurt Havva Taspinar (Universitas Hamzanwadi, 2026)
Reading comprehension in EFL contexts requires students to move beyond locating explicit information toward actively reconstructing and communicating textual meaning. This study investigated the effectiveness of Instagram-based oral retelling in improving EFL students’ reading comprehension and explored students’ perceptions of the learning experience. Using a mixed-methods design, the study employed a pre-experimental one-group pre-test and post-test design supported by open-ended reflective questionnaire responses. The participants were 32 second-semester EFL undergraduate students from a private university in Kudus, Central Java, Indonesia. During a five-week intervention, students read narrative texts, prepared oral retellings, recorded videos, posted them on Instagram, and received feedback from the lecturer. Quantitative data from the reading comprehension pre-test and post-test were analyzed using a paired-sample t-test, while qualitative responses were analyzed thematically. The results showed a significant improvement in students’ reading comprehension, with the mean score increasing from 71.25 in the pre-test to 82.66 in the post-test. The paired-sample t-test confirmed a statistically significant difference, t(31) = -9.397, p < .001. Students’ reflective responses indicated that Instagram-based oral retelling made reading more engaging, purposeful, and interactive. The activity encouraged repeated reading, vocabulary awareness, pronunciation practice, confidence building, creativity, and peer interaction. However, students also reported challenges, including unstable internet connections, long video-uploading times, unfamiliar vocabulary, pronunciation difficulties, and initial embarrassment when posting videos publicly. These findings suggest that Instagram-based oral retelling can transform reading comprehension practice into a more active, multimodal, and audience-oriented learning experience when supported by clear guidance, technical flexibility, and appropriate linguistic scaffolding.